Identifying classification systems regarding vascular access for haemodialysis: protocol for a scoping review - Petr Waldauf; Michael Corr; Stephen O’neill; Katerina Lawrie; Jan Bafrnec; Peter Balaz (BMJ Open)
Introduction Classifications are important clinical tools that enable data arrangement, patient categorisation and comparative research. The care of patients with end-stage renal disease who have vascular access requires collaboration of several specialists. In such a field, where several different specialties overlap, strong evidence and well-grounded recommendations for good practice are essential. In this protocol, we aim to search the literature to identify classification systems regarding vascular access for haemodialysis. This protocol serves as a pragmatic tool for setting a systematic approach using scoping review methodology. It also aims to make the study transparent and avoid potential duplication.Methods and analysis We will follow the Joanna Briggs Institute methodology for the conduct of scoping reviews during the course of the proposed review. Scopus, Web of Science, PubMed, Google Scholar and the ClinicalTrials.gov registry will be searched by two researchers. Titles and abstracts will be screened and articles featuring classifications regarding vascular access for haemodialysis will be eligible for full-text analysis. There will be no age, sex or race limitation for the study populations. The title and abstract (if abstract available) must be in English but there will be no language restrictions for full-text review. Databases will be searched from inception to the date of search. All patients indicated for creation or placement of vascular access will be eligible, as well as patients with already existing vascular access. Classifications regarding preprocedural assessment, vascular access insertion or creation, complications and their management will be included in the study. Classifications regarding peritoneal dialysis will not be eligible. A comprehensive summary of the available evidence will be presented.Ethics and dissemination The protocol and the review are exempt from ethical approval as there is no direct patient involvement and the review will summarise data from already published literature. The final article will be submitted to a peer-reviewed scientific journal.